Detection of Mutated K-ras DNA in Urine, Plasma, and Serum of Patients with Colorectal Carcinoma or Adenomatous Polyps - Su, Ying-Hsiu (2008)
Our previous studies demonstrated that urine contains DNA derived from the circulation and that this DNA originated, in part, from organ sites and tumors distal to the urinary tract. To explore the potential use of DNA from urine as compared to other body fluids as a source for circulating DNA for cancer detection, the DNA concentration and the frequency of detection of mutated Kristin-ras (K-ras) DNA in serum, plasma, and urine were examined. The concentration of DNA in the urine was similar to that in the serum, but the DNA concentration in plasma was significantly lower than in either urine or serum (P < 0.05). When DNA derived from 10 μL of body fluid was used in each mutation assay, the detection frequency of mutated K-ras DNA was comparable among serum, plasma, and urine. However, when DNA derived from 200 μL of body fluid was used, the incidence of detecting mutated K-ras DNA in urine was significant higher (95%) than in either serum (35%) or plasma (40%) (P < 0.0005), suggesting that inhibitory factors in serum/plasma may be more limiting than in urine. The use and practicality of urine as a source of circulating DNA for cancer detection are discussed.